Longitudinal Network Relationships Between Symptoms of Deviant Peer Affiliation and Internet Gaming Disorder in Adolescents: Prospective Cohort Study - Gao, Tingting; Qian, Fengtong; Li, Rui; Lyu, Yimeng; Su, Yingying (Journal of medical Internet research, 2025)
Previous studies have revealed that deviant peer affiliation (DPA) and internet gaming disorder (IGD) are highly related and often co-occur. Nevertheless, the dynamic interactions among these symptoms, their bidirectional effects, and the underlying mechanisms contributing to their persistence remain poorly understood. Most existing research relies on cross-sectional designs or examines aggregated scores, limiting the ability to detect time-dependent symptom interactions. In particular, prior studies overlook the complex bidirectional relationships between specific IGD and DPA symptoms over time. As adolescence is a developmental period marked by rapid changes in peer relationships and behavioral regulation, distinguishing temporal associations between specific DPA and IGD symptoms at both the within- and between-person levels is important for clarifying mechanisms of their co-occurrence and informing personalized intervention strategies. This study aims to examine the temporal and directional relationships between DPA and IGD at the symptom level and differentiate within-person dynamics from between-person differences in their co-occurrence. By focusing on specific symptom-level interactions, this study aims to unravel whether changes in one behavior drive changes in the other over time and to clarify whether their relationship is more influenced by individual changes or stable characteristics. Data were drawn from a prospective cohort study including a representative sample of 3296 adolescents. Cross-lagged panel networks analysis was used to explore the directional and temporal associations between individual symptoms of DPA and IGD across time, disentangling within-person dynamics from between-person differences as well as identifying the most influential symptoms that drive their interactions over time. At the within-person level, several IGD symptoms exhibited predictive effects on subsequent DPA symptoms. Specifically, jeopardized school or work performance due to gaming (IGD10) predicted deviant peer behaviors, including friends' smoking (DPA1; β=.403) and friends' stealing (DPA4; β=.393). In addition, losing significant relationships due to gaming (IGD9) strongly predicted friends' misbehavior (DPA6; β=.475). However, no significant between-person associations were observed, suggesting that the co-occurrence of IGD and DPA is not primarily explained by stable trait-level differences, but rather by dynamic, time-varying processes occurring within individuals. Our findings provided valuable insights into the complex relationships between DPA and IGD symptoms, highlighting that the IGD-DPA relationship is primarily driven by within-person dynamic changes rather than stable trait-level differences. This suggests that interventions aimed at reducing IGD risk should focus on addressing the dynamic, time-dependent interactions between gaming behaviors and peer relationships. Prevention programs should focus on healthy peer relationships and adaptive coping strategies to reduce IGD risk and its social consequences. Targeted interventions could disrupt the cycle of maladaptive behavior by focusing on improving both peer and social functioning during critical developmental periods, ultimately preventing the exacerbation of these behavioral issues over time.